IPTEKS BAGI MASYARAKAT (IbM) KLASTER INDUSTRI KECIL MAKANAN KHAS DI CANDI MUARO JAMBI - Sri Marmoah; Kasiono Kasiono (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Candi Muaro Jambi sights in Muaro Sebo Muaro Jambi Regency is a tourist attraction that has known both locally as well as nationally. The activities of the community in skim ipteks for society (IbM) aims to identify the typical food of the temple as an icon of Muaro Jambi and is expected to increase the number of tourists visiting the temple as well as a aims to economically empower the society around candi Muaro Jambi. This activity is carried out in five phases, namely: the first orientation and socialization which is held in the village of Jelmu and the village of Muaro Jambi. Both surveys and market potential in the area of candi Muaro Jambi in order of determination of typical temple as towing tourists. The action of the market survey is an activity that is sustainable in tourists travelling in monitor culinary. Results of the third production through training and practice of making fish crackers that were held in the village of Jelmu and the village of Muaro Jambi. Principal activity is the production of action to give birth to the temple area of the culinary icon Muaro Jambi in particular making of "krupuk" fish. At this stage, Ipteks for the community built to bore the iconic tourist Area Temple specialties Muaro Jambi through training. The four stages of packaging. Action packaging is an activity after the stage production. In the tourist activity, packaging is the part that is not integral to attracting tourists. Packaging activities related to packing, presentation, and supply. The five stages of marketing. Action marketing is key to the success of the whole process effortless. Marketing strategies need to be examined together with the involved participants and obtain the advice of the other stakeholders. Its activities in the form of discussions facilitated by the managers of the temple as the parties keep the synergy program development in the area of candi Muaro Jambi. In the ipteks activities for the Community (IbM) is carried out in a partnership with two partners, namely, the village of Muaro Jambi PKK as a partner I and Kube Orchid Village Jelmu as partners II. Plan follow-up (RTL) after connecting trainees in the program Ipteks for the community is doing a promotion more broadly and reinforcement. The activities of the community is very helpful in empowering the community in particular to empower mothers in utilizing their spare time and have added value economically.Keywords:  Ipteks for the public, typical food, candi Muaro Jambi.